Awareness and use of the Society for Ecological Restoration's International Principles and Standards for the Practice of Ecological Restoration in Canada. Issue 1 (27th September 2022) - Voicescu, Sonia A.; Lane, John‐Francis; Cooke, Steven J.; Higgs, Eric; Fisher, Alina C.; Rochefort, Line; Shackelford, Nancy; Murphy, Stephen
Abstract : The Society for Ecological Restoration (SER) published the second edition of its International Principles and Standards for the Practice of Ecological Restoration in 2019. We conducted a pan‐Canadian study using semi‐structured interviews with restoration professionals to explore the extent to which restoration practitioners are aware of the document and use it. Overall, we found that direct uptake of the document by practitioners was lower than expected, with approximately 37.7% of all participants that were both aware of and consulting the publication for guidance in their practice of ecological restoration. This is due in part to low awareness of the document itself, with only a small majority (56.5%) of interviewees being aware of it. Other reasons listed by practitioners such as the structure of the publication, its added value, and its suitability for on‐the‐ground work revealed why some individuals aware of the existence of the document still failed to consult it. Here, we present a more nuanced assessment of these observations and share our findings with the ecological restoration community to address this disconnection. With intensifying pressures to achieve restoration success internationally, SER's guidance is critical. We analyze why it seems guidance from SER is not being taken up as fully as it might, and ways in which future versions may be improved.